ANALYZING THE EFFECTIVENESS OF MARKETING STRATEGIES IN INCREASING RICE SALES: A CASE STUDY OF CV SURYA AGRO TANI USING 7P MARKETING MIX AND SWOT ANALYSIS - Damayanti, Asty; Kumar, Suresh (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
This study aims to analyze the marketing strategies employed to increase rice product sales at CV SuryaAgro Tani, focusing on the company's use of the 7Ps marketing mix framework (Product, Price, Place,Promotion, People, Process, Physical Environment). Additionally, the research employs a SWOT analysis(Strengths, Weaknesses, Opportunities, Threats) to evaluate the effectiveness of these strategies and topropose actionable recommendations for enhancing sales performance. This study was initiated in responseto a significant decline in rice sales over three consecutive months, driven by both internal and externalfactors. Through this analysis, the research contributes to both academic literature and practical solutionsfor overcoming such challenges in the agricultural industry. The study provides valuable insights foragribusinesses like CV Surya Agro Tani, demonstrating how an effective use of the marketing mix,combined with a well-structured SWOT analysis, can be leveraged to improve sales performance. Thefindings suggest that companies in similar contexts can adopt an aggressive strategy to capitalize on theirstrengths and external opportunities, offering a roadmap for reversing declining sales trends. The researchalso highlights the broader social impact of effective marketing strategies in the agricultural sector,particularly in helping small and medium-sized enterprises (SMEs) like CV Surya Agro Tani thrive despitemarket fluctuations. By improving sales, such businesses can contribute to local economic stability,employment, and food security. This study is unique in applying the 7Ps marketing mix and SWOT analysisspecifically to the rice market at CV Surya Agro Tani. It offers a novel contribution to the academicliterature on marketing strategies in the agricultural industry, as prior research has predominantly focusedon other business sectors. Furthermore, it provides practical insights that can be applied to similaragribusinesses facing comparable challenges.Keywords: Marketing Strategy, 7Ps, SWOT Analysis, Sales Performance, Agribusiness, CV Surya AgroTani, Rice Products